Sympathetic skin response (SSR) in pediatric Guillain–Barré syndrome - Jin, Mei; Liu, Jing; Liu, Kang; Zhao, Libo; Zhao, Ziwei; Sun, Suzhen (Frontiers in Neurology, 2023)
Introduction: The present study explores sympathetic skin response (SSR) characteristics in children with Guillain-Barré syndrome (GBS) and analyzes the value of early diagnosis and prognostic evaluation in GBS complicated with autonomic dysfunction (AD). Methods: In this prospective study, 25 children with GBS and 30 healthy controls (HCs) were enrolled. The SSR responses of the two groups were compared. The SSR and nerve conduction study (NCS) results were compared in patients with GBS, and the correlation between the SSR and clinical characteristics was analyzed. Results: The GBS group consisted of six patients (24%) with mechanical ventilation, 17 patients (66.7%) with AD, 18 patients (72%) with abnormal SSR, and 13 patients (52%) with AD combined with SSR abnormalities. SSR latency of GBS group in the lower limbs showed statistical difference as comparing to HCs (P<0.05). There was no statistically significant difference between the SSR and NCS results in the acute phase of GBS (P > 0.05), and there was no significant difference in the AD and Hughes functional grades at nadir between the abnormal and normal SSR groups (P>0.05). There was a statistically significant difference between the SSR and NCS tests during the recovery phase (P =0.003). Abnormal SSR mainly occurred in the acute inflammatory demyelinating polyradiculoneuropathy (AIDP). In addition, the SSR of all pediatric GBS patients with poor prognosis 1 month after symptom onset was abnormal. Conclusion: Children with GBS have a higher incidence of AD. SSR could be used for the early diagnosis and follow-up of GBS and may also be helpful for evaluating disease severity and short-term prognosis.